EDUCATION OF INFORMATICS AND INFORMATION AS EDUCATIONAL SYSTEM COMPONENT - PIECUCH, Aleksander (Trends in education, 2009)
This article talk over a problems connected with teaching of informatics subjects in polish schools. Fast out of date on the ground of technical progress in teaching program of informatics subjects from bad to worse are able to rise modernity criterion. This article account for discussion about this problematic.
Keywords: information technology; information science; technique; informatical capacity.